NEW METALLOGENIC ASPECTS OF SKARNS FROM THE PITKARANTA ORE PROVINCE - Василий Иванович Иващенко; Анатолий Иванович Голубев; Vasily Ivashchenko; Anatoly Golubev (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2015)
The original results of high-precision mineralogical and geochemical studies of the skarn ore samples from the Pitkaranta Ore Province are reported. The main mineral ore assemblages, including 58 minerals revealed there for the first time (roquesite, angelaite, pavonite, cervelleite, jalpaite, zavaritskite, stannoidite, etc.), are described. Twenty-seven of them have not been found in Karelia before. Evidence for metallogenic significance of roquesite (CulnS2), indium-bearing (1.0 %) sphalerite, native gold, electrum and large groups of silver, bismuth and tellurium minerals in Pitkaranta ores is presented. This, together with high concentrations of In (up to 0.33 %), Ag (up to 0.2 %), Au (up 1.1 g/t) and platinoids (up to 0.4 g/t) in the ore skarns, shows that the province has a high metallogenic potential. The Pitkaranta Ore Province is one of the most promising areas in Russia in terms of indium concentration (-100 g/t) and expected indium resources (2400 t). The indications of platinum in the Riphean sandstones of the area are discussed. A comparison with the Korostensky massif and Rogoland complex is made and the Salmi anorthosite-rapakivi granite massif is preliminarily assessed for rare-earth and Ti-P mineralization.